1997
DOI: 10.1046/j.1365-2141.1997.4803282.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP phosphodiesterases in human lymphocytes

Abstract: Summary. The function of lymphocytes, like platelets, has been shown to be inhibited by agents which increase intracellular cyclic AMP. Two high-affinity cAMP phosphodiesterases (PDEs), the cyclic GMP-inhibited cAMP phosphodiesterase, PDE3, and the cAMP-specific phosphodiesterase PDE4, are known to regulate cAMP concentration in haemopoietic cells by degrading cAMP to AMP. We characterized the relative contribution of the two PDEs to total lymphocyte PDE activity. We then determined which of the different gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 20 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…In addition to PDE4, lymphocytes express PDE3 activity. 39 However, the PDE3 inhibitor trequinsin caused little effect on CEM cell growth, even at concentrations well above the inhibitory concentration of 50% (IC 50 ) for PDE3 activity in vitro of 0.3 nM ( Figure 1G). Similarly, the PDE1-specific inhibitor vinpocetine induced no growth suppression of CEM cells until the drug rose to concentrations at which PDE subclass selectivity is lost (IC 50 for PDE1 activity in vitro ϭ 20 M; Figure 1H).…”
Section: Cell Growth Is Suppressed By Inhibition Of Pde4 Activity Butmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to PDE4, lymphocytes express PDE3 activity. 39 However, the PDE3 inhibitor trequinsin caused little effect on CEM cell growth, even at concentrations well above the inhibitory concentration of 50% (IC 50 ) for PDE3 activity in vitro of 0.3 nM ( Figure 1G). Similarly, the PDE1-specific inhibitor vinpocetine induced no growth suppression of CEM cells until the drug rose to concentrations at which PDE subclass selectivity is lost (IC 50 for PDE1 activity in vitro ϭ 20 M; Figure 1H).…”
Section: Cell Growth Is Suppressed By Inhibition Of Pde4 Activity Butmentioning
confidence: 99%
“…[30][31][32] Normal lymphocytes and several lymphoid leukemia cell lines express at least 2 high-affinity cAMP PDEs, cyclic guanosine monophosphate (cGMP)-inhibited cAMP PDE (PDE3) and the cAMP-specific PDE (PDE4), whereas PDE4 is dominant in monocytes and neutrophils and PDE3 in platelets. [33][34][35][36][37][38][39][40] Vinpocetine, an inhibitor of PDE1, induces apoptosis in ALL cells. 41 Rolipram, an inhibitor of PDE4 enzymes, selectively induces apoptosis in CLL patient cells in vitro.…”
mentioning
confidence: 99%
“…At a minimum, lymphoid cells express PDE1B, PDE3B, PDE4A, B, and D, and PDE7A; all enzymes that can catabolize 3Ј:5Ј cyclic adenosine monophosphate (cAMP). [1][2][3][4][5] In studies of the mature B-cell malignancy B-cell chronic lymphocytic leukemia (B-CLL), we and others have found that both nonspecific PDE inhibitors such as theophylline and the PDE4-specific inhibitor rolipram induce apoptosis in leukemic cells over a 48-to 72-hour period. [6][7][8] While rolipram also induces apoptosis in peripheral B cells, albeit superimposed on a high normal basal apoptotic rate, the same agent has little or no apoptotic effect on peripheral T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Following stimulation, intracellular cAMP levels are rapidly down-regulated by phosphodiesterases that transform cAMP into inactive AMP (29). A range of downstream effects of the cAMP signal have been described in different immune cells, regulated by strict localization of the signal (reviewed in reference 36).…”
mentioning
confidence: 99%